2020
DOI: 10.1038/s41420-020-00303-0
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of FBXO22 in carcinogenesis

Abstract: The F-box protein 22 (FBXO22), one of F-box proteins, has been identified to be critically involved in carcinogenesis. FBXO22 promotes proliferation in breast cancer and lung cancer, but suppresses migration and metastasis. FBXO22 exerts oncogenetic functions via promoting the ubiquitination and degradation of its substrates, including KDM4A, KDM4B, methylated p53, p21, KLF4, LKB1, Snail, CD147, Bach1, PTEN, and HDM2. FBXO22 is also regulated by several regulatory factors such as p53, miR-155, SNHG14, and circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 50 publications
(82 reference statements)
0
21
0
Order By: Relevance
“…Accumulating evidence suggested that FBXO22 exerts its oncogenic functions through mediating the ubiquitination and degradation of substrates in many human malignancies ( 40 ). However, the roles it plays in different tumors is inconsistent in physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggested that FBXO22 exerts its oncogenic functions through mediating the ubiquitination and degradation of substrates in many human malignancies ( 40 ). However, the roles it plays in different tumors is inconsistent in physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have shown that FBXO22 is involved in oncogenesis owing to its ubiquitination activity and the subsequent degradation of multiple proteins ( 2 ), the means by which FBXO22 affects tumor growth by regulating substrate protein levels was largely unknown. Thus, we identified 23 FBXO22-binding proteins using the STRING database and literature search; these were all significantly enriched in cell cycle-negative regulation and ubiquitination pathways.…”
Section: Discussionmentioning
confidence: 99%
“…F-Box only protein 22 (FBXO22), a PTM regulator, is a member of the F-box protein family with E3 ligase activity ( 1 ). Recently, FBXO22 has shown to mediate ubiquitination of multiple proteins and has been linked to tumorigenesis ( 2 ). FBXO22 is involved in cell development and differentiation, including in cancer, by controlling the stability of lysine demethylase 4A (KDM4A) ( 3 ); FBXO22 ubiquitylates p53 and forms a complex with KDM4A to regulate cellular senescence ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several biological functions of FBXO22 in tumorigenesis have been determined in recent years. According to the different degradation target proteins of the FBXO22 complex, it plays a corresponding function in cells ( Cheng et al, 2020 ). FBXO22 promotes tumorigenesis by degrading nuclear PTEN ( Ge et al, 2020 ), promotes lung cancer by mediating the polyubiquitination with the inactivation of LKB1 ( Zhu et al, 2019 ) and Bach1 ( Lignitto et al, 2019 ), and promotes the development of hepatocellular carcinoma by regulating the ubiquitination and degradation of p21 ( Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%